Promotional Media Design in Social Media Using Photography to Pour And Peace: Perancangan Media Promosi Dalam Media Sosial menggunakan Fotografi Untuk Pour And Peace - Nurfitri, Rina; Rahmansyah, Anggi (Procedia of Social Sciences and Humanities, 2022)
The design of social media promotions is focused on one beverage brand, namely "Pour And Peace". "Pour And Peace" is a beverage brand originating from Pekanbaru City and has a good appeal among teenagers to the elderly. With the uniqueness of the drink that uses coffee beans typical of the Sumatran region and the visuals on the product, it is possible to promote the "Pour And Peace" product to strengthen the image and awareness of the target audience for local products. The “Pour And Peace” product has its own uniqueness with its visual appearance that looks like a drink containing alcohol in its packaging. But actually this drink is coffee beer or so-called coffee soda. "Pour And Peace" itself makes the design more unique because the main target market is young people or teenagers. The use of photography is very possible to be used as a way to promote "Pour And Peace" products, by taking pictures made more expressive, with product photo techniques, still life, angel placement, composition and so on. This design is made using a marketing design method that identifies product data and marketing data which are finally analyzed. After the identification process, the author determines the synthesis and design concept which consists of media planning and creative planning so as to produce a design concept concept. The final design results are determined in the form of promotional media in the form of photos and videos published on social media. The results of this design are expected to introduce coffee beer products